Innovations in Transportation: research and policy lessons of recent successful cases - Bert Van Wee (European Regional Science Association (ERSA), 2003)
To reduce environmental impact of transport and congestion several kinds innovations can play an important role. Many examples of incremental innovations exist, but the transport sector does not have a good record of more radical innovations. In the literature on innovations it has been concluded often that a traditional top-down, vertical process might often be less successful than a more horizontal, systemic approach, in which many actors are involved. This paper focuses on successful innovations in transport that have been realised. Seven cases studies were carried out, focusing on the goals, the role of actors, the role of research, and the instruments used. The main conclusions of the research are firstly that the services described can certainly result in local improvements in nuisance from parked and driven vehicles, noise and air pollution. Secondly, the local municipalities have played an important role in the introduction of the new services. Thirdly, in some cases the role of only one person (or a few persons) had a huge impact in the introduction of the services. Fourthly, in several cases the solution was not as much in expensive, high-tech measures, but in very simple but creative ways of using existing possibilities, e.g. the park-and-ride service for shopping in Utrecht using an existing parking lot. The service itself does not involve much more than offering a parking place and a bus to the centre. Fifthly, the role of research differs considerably among the innovations, sometimes being of crucial importance, but sometimes hardly relevant. Sixth, all functions that play a crucial role in the management of present-day innovation processes, as presented by Smits and Kuhlmann (2002), appear in some cases, though not in all cases. The management of interfaces brought actors together. The organising systems often did not exist before. Learning and experimenting plaid an important role in several cases. The demand articulation was very important in some of the cases: the services were organised starting from the perspective of the users. The role of providing an infrastructure for strategic intelligence in the cases has been limited.
Keywords: 330